PEDAGOGICAL TECHNOLOGY IN THE EDUCATIONAL PROCESS OF "MILITARY EDUCATION BEFORE THE DRAFT" - Khasanov Akhadjon Tursinovich; Аzimov Adaham Melikuzievich (Journals Park Publishing, 2022)
To Khasanov’s article “Pedagogical technology in the process of teaching academic course “Until military education” studied questions incoming in the academic process of pedagogical technology on preparing the specialists until military education in the specialized faculties of the higher humanitarian schools.
Keywords: pedagogical technology, innovation, militarian skillful, conception